Impact of integrated weed control methods on yield performance and sustainable weed suppression in sugar beet (Beta vulgaris L.) - Küçük, Ömer; Bozdoğan, Olcay (Frontiers in Plant Science, 2026)
Weed infestation remains a major constraint limiting the yield potential of sugar beet (Beta vulgaris L.) worldwide. Weeds compete with the crop for light, water, and nutrients, and if not effectively managed, they can cause severe yield and quality losses. Developing sustainable and efficient weed management strategies is therefore essential for maintaining crop productivity and reducing economic losses in sugar beet cultivation. This two-year field experiment (2020–2021) was conducted in Yeni Village, Doğanşehir District, Malatya Province, Türkiye, to assess the impact of various weed control methods on yield performance and weed suppression. The study employed a randomized complete block design with twelve treatments and four replications, including weedy and weed-free controls, herbicide applications, and combinations of herbicides with hand hoeing or power tillage. Yield components (total plant weight, root weight, leaf weight, root diameter, and plant length) and weed parameters (density, cover, fresh and dry weight) were recorded and statistically analysed. The highest yield was obtained from the weed-free control, followed by the integrated treatments combining pre-emergence herbicide (700 g L-1 metamitron) with one or two hand hoeings. These methods reduced the dry weight of the weeds by between 90.14% and 96.11% and increased yield by up to 365% compared with the weedy control. Herbicide-only treatments were less effective in sustaining yield and suppressing weeds. The findings emphasize that integrating chemical and mechanical control methods provides superior and more sustainable weed suppression, underscoring the importance of integrated weed management in sugar beet production systems.